Positive airway pressure (PAP) treatment reduces glycated hemoglobin (HbA1c) levels in obstructive sleep apnea patients with concomitant weight loss: Longitudinal data from the ESADA. (14th May 2021) - Tasbakan, Mehmet Sezai; Grote, Ludger; Hedner, Jan; Kvamme, John Arthur; Verbraecken, Johan; McNicholas, Walter T.; Roisman, Gabriel; Tkacova, Ruzena; Bonsignore, Maria R.; Saaresranta, Tarja; Steiropoulos, Paschalis; Marrone, Oreste; et al.
Summary: Patients with obstructive sleep apnea (OSA) are at increased risk of developing metabolic disease such as diabetes. The effects of positive airway pressure on glycemic control are contradictory. We therefore evaluated the change in glycated hemoglobin (HbA1c) in a large cohort of OSA patients after long‐term treatment with positive airway pressure. HbA1c levels were assessed in a subsample of the European Sleep Apnea Database [n=1608] at baseline and at long‐term follow up with positive airway pressure therapy (mean 378.9±423.0 days). In a regression analysis, treatment response was controlled for important confounders. Overall, HbA1c decreased from 5.98±1.01% to 5.93±0.98% (p=0.001). Patient subgroups with a more pronounced HbA1c response included patients with diabetes (−0.15±1.02, p=0.019), those with severe OSA baseline (−0.10±0.68, p=0.005), those with morbid obesity (−0.20±0.81, p<0.001). The strongest HbA1c reduction was observed in patients with a concomitant weight reduction >5 kilos (−0.38±0.99, p<0.001). In robust regression analysis, severe OSA (p=0.038) and morbid obesity (p=0.005) at baseline, and weight reduction >5 kilos (p<0.001) during follow up were independently associated with a reduction of HbA1c following PAP treatment. In contrast, PAP treatment alone without weight reduction was not associated with significant Hb1Ac reduction. In conclusion, positive airway pressure therapy is associated with HbA1c reduction in patients with severe OSA, in morbidly obese patients. and most obviously in those with significant weight lost during the follow‐up. Our study underlines the importance to combine positive airway pressure use with adjustments in lifestyle to substantially modify metabolic complications in OSA.